Bentuk Pembiayaan Usahatani Ditinjau dari Perspektif Islam di Kecamatan Pringgasela Kabupaten Lombok Timur - Nur Eliza Samudra Dewi; Akhmad Jufri; Moh. Huzaini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyse agricultural financing in Pringgasela Subdistrict, East Lombok Regency, and to analyse how financing is viewed from an Islamic perspective. This study is qualitative in nature. Data collection techniques include interviews, observation, and documentation. Informants for this study were selected using purposive and snowball sampling techniques. The data validity checking technique used by the author in this study was triangulation, and the data analysis method used was the interactive Miles and Huberman method, which consists of data collection, data reduction, data presentation, and conclusion drawing. Based on the results of the research, it can be seen that there are two types of agricultural financing carried out by farmers, namely financing with their own capital and financing using capital from middlemen or collectors (borrowing or Qardh). Financing with own capital involves having other businesses besides farming that are used as sources of income to finance farming needs, such as grain trading, rice milling, and drying businesses. Meanwhile, financing from middlemen takes the form of loans of money. Loans in the form of money provided by investors or middlemen do not incur additional charges or interest, but middlemen only reap profits when harvest time arrives because they are the ones who sell the farmers' crops, allowing them to determine the prices paid to farmers. Both types of financing are in accordance with the principles of Islamic economics.